Attention deficit/hyperactivity disorder (ADHD) is associated with altered heart rate asymmetry - Tonhajzerová, I; Ondrejka, I; Farský, I; Višňovcová, Z; Mešťaník, M; Javorka, M; Jurko, A; Čalkovská, A (Physiological research, 2014)
Attention deficit/hyperactivity disorder (ADHD) is associated with complex neurocardiac integrity. We aimed to study heart rate time asymmetry as a nonlinear qualitative feature of heart rate variability indicating complexity of cardiac autonomic control at rest and in response to physiological stress (orthostasis) in children suffering from ADHD. Twenty boys with ADHD and 20 healthy age-matched boys at the age of 8 to 12 years were examined. The continuous ECG was recorded in a supine position and during postural change from lying to standing (orthostasis). Time irreversibility indices - Porta's (P%), Guzik's (G%) and Ehlers' (E) - were evaluated. Our analysis showed significantly reduced heart rate asymmetry indices at rest (P%: 49.8 % vs. 52.2 %; G%: 50.2 % vs. 53.2 %; p<0.02), and in response to orthostatic load (P%: 52.4 % vs. 54.5 %, G%: 52.3 % vs. 54.5 %; p<0.05) associated with tachycardia in ADHD children compared to controls. Concluding, our study firstly revealed the altered heart rate asymmetry pattern in children suffering from ADHD at rest as well as in response to posture change from lying to standing (orthostasis). These findings might reflect an abnormal complex cardiac regulatory system as a potential mechanism leading to later cardiac adverse outcomes in ADHD.
Keywords: Child; hyperkinetická porucha; studie případů a kontrol; Attention Deficit Disorder with Hyperactivity; postura těla; Heart Rate; Humans; Case-Control Studies; srdeční frekvence; lidé; Heart; dítě; srdce; Posture